2021
DOI: 10.3389/fendo.2021.760860
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Roles of T Cells in the Pathogenesis of Nonalcoholic Steatohepatitis and Hepatocellular Carcinoma

Abstract: Nonalcoholic fatty liver disease (NAFLD) has become the most common chronic liver disease worldwide. A significant proportion of patients with NAFLD develop a progressive inflammatory condition termed nonalcoholic steatohepatitis (NASH), which may eventually advance to cirrhosis and hepatocellular carcinoma (HCC). NASH is characterized by steatosis, hepatocyte ballooning, and lobular inflammation. Heightened immune cell infiltration is a hallmark of NASH, yet the mechanisms whereby hepatic inflammation occurs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 126 publications
2
29
1
Order By: Relevance
“…The role of CD4+ T cells in NAFLD is less clear and studies using single-cell technologies will likely provide novel insights in the coming years. Numerous studies reported that Th1 and Th17 cells are elevated in patients with NASH [135]. Particularly, IFN-γ-expressing CD4 T cells were enriched in NASH and mice deficient in IFN-γ fed the MCD diet had milder steatohepatitis and J o u r n a l P r e -p r o o f reduced infiltration of inflammatory macrophages [136,137].…”
Section: Inflammation In Nash Is Driven By "Auto-aggressive" Effector...mentioning
confidence: 99%
“…The role of CD4+ T cells in NAFLD is less clear and studies using single-cell technologies will likely provide novel insights in the coming years. Numerous studies reported that Th1 and Th17 cells are elevated in patients with NASH [135]. Particularly, IFN-γ-expressing CD4 T cells were enriched in NASH and mice deficient in IFN-γ fed the MCD diet had milder steatohepatitis and J o u r n a l P r e -p r o o f reduced infiltration of inflammatory macrophages [136,137].…”
Section: Inflammation In Nash Is Driven By "Auto-aggressive" Effector...mentioning
confidence: 99%
“…Since Th17 lineage regulates metabolism and adipogenesis, proinflammatory cytokines could influence the onset of NAFLD ( 13 ). The major role of Th-17 lineage in liver were thought to be highly involved in the progression from NAFLD to the severe subtype of Nonalcoholic Steatohepatitis (NASH) ( 37 , 38 ). Additionally, abnormalities in visceral adipose tissue are considered to be involved in the pathogenesis of both diseases ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…role: they can cross-communicate with neutrophils, natural killer cells, innate lymphoid cells, and lymphocytes, coordinating cell recruitment, activation, and subsequent fate of hepatic inflammation (29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%